The Riskbank's forecasting performance - Michael F. Andersson; Gustav Karlsson; Josef Svensson (Sveriges Riksbank, 2007)
This paper describes the official Riksbank forecasts for the period 2000-06. The forecast variables are those that are important for monetary policy analysis, i.e. inflation, GDP, productivity, employment, labour force, unemployment and financial variables such as interest rate and foreign exchange rate. The Riksbank's forecasts are presented and analyzed and compared with alternative forecasts, that is, those from other institutions and simple statistical models. One important message from the study is that macroeconomic forecasts are associated with an appreciable uncertainty; the forecast errors are often sizeable. The forecast memory, defined as how far the forecasts are more informative than the variables unconditional mean, is usually limited to the first year. Furthermore, we find that the inflation forecasts exhibit several appealing features, such as a predictability memory that (possibly) includes the second year, relatively low RMSE and weak efficiency. The forecasts for the investigated real variables are shown to be less precise and they have a shorter forecast memory. The exchange rate predictions demonstrate the least accurate (of the investigated variables) forecasts. Compared to other forecasters, the Riksbank's predictions are often more accurate. This holds for a comparison with the National Institute of Economic Research, even though the differences are statistically insignificant, as well as for a comparison with the participants in the Consensus Forecasts panel, where the Riksbank's predictions often are among the best. We also find indications that misjudgements for productivity growth have had effects on forecasts for both inflation and GDP, but the results suggest that the Riksbank has considered available information in an acceptable fashion. This is also true for the undertaken revisions (from one forecast occasion to another) of the published forecasts.
Keywords: E52; E37; E27; 330; Judgements; Forecast Evaluation; Central Bank; Inflation; GDP; RMSE; Zentralbank; Konjunkturprognose; Konjunkturindikator; Bewertung; Schweden